Educazione scientifica e/o educazione ambientale - Conti, Paola (Chimica nella Scuola, 2024)
This contribution describes a pedagogical way of addressing the problem of the environmental emergency that combines the method for teaching scientific education with an ecological perspective based on attitudes and behaviors. Starting from knowledge and discovery it is, in fact, possible to build emotional bonds with what we are observing. This is a first approach to the issue which, however, represents an attempt to underline some points useful to start the work in this direction.